On Suzuki and Wardowski-Type Contraction Multivalued Mappings in Partial Symmetric Spaces - Mohammad Asim; Hassen Aydi; Mohammad Imdad (Journal of Function Spaces)
The purpose of this paper is to provide some fixed-point results for Suzuki and Wardowski-type contraction multivalued mappings in partial symmetric spaces. We give some examples to support and substantiate the developed notions and obtained results. Also, we use one of our main results to establish the existence and uniqueness of the solution for a system of integral inclusions.